THE DIVERSITY Of FRUIT FLIES IN RED GUAVA CROPS AND PARASITOID PARASITIZATION LEVEL IN DISTRICT DELI SERDANG - Sari, Putri Mustika; Bakti, Darma; Tobing, Maryani Cyccu (Journal of Community Research and Service, 2017)
AbstractMorphological and Molecular of Identification Bactrocera sp. (Diptera: Tephritidae) in 5 Location of Red Guava Crops District Deli Serdang. Fruit flies are a concern in the world because they are an important pest in fruits. Seven species of fruit flies (Bactrocera carambolae, Bactrocera papayae, Bactrocera curcubitae, Bactrocera caudata, Bactrocera albistrigata, Bactrocera tau, Bactrocera umbrosa) have been identified from the morphological identification of fruit flies in LIPI. The fruit fly is obtained from trapping with methyl eugenol, cocoa waste processing, and a mixture of both. Found 2 species of parasitoid (Psytallia sp. near Walker; Psytallia sp. near Walkeri) from the rearing of fruit that was attacked at five locations of red guava plantation district Deli Serdang.Keywords : Bactrocera spp., morphology, atractant, parasitoid